Insight into protein crosslinking and casein polymerization in pre- and posthydrolyzed lactose-free ultra-high-temperature milk during long-term storage - Lotte J. Knudsen; Valentin Rauh; Jannik N. Pedersen; Peter Dekker; Daniel E. Otzen; Lotte B. Larsen; Søren D-H. Nielsen (Journal of Dairy Science)
ABSTRACT: During processing and storage of both conventional and lactose-hydrolyzed UHT milk (LHM), aggregation of milk proteins occurs. Protein aggregation can inter alia occur via nonreducible covalent cross-links derived from either Maillard or dehydroalanine (DHA) pathways. To study this further in relation to processing method and lactase enzyme purity, LHM was produced using 3 different lactase preparations, with lactase enzymes added in a dairy setting either before (prehydrolysis) or after (posthydrolysis) UHT treatment. The prepared LHM types were subsequently stored at either 25°C or 35°C for up to one year. Mass spectrometry was used to absolutely quantify the level of furosine, N-ε-(carboxymethyl)lysine, N-ε-(carboxyethyl)lysine, lanthionine, and lysinoalanine in these products using a newly developed method on triple quadrupole for these processing-induced markers. The results showed higher levels of Maillard-related processing markers in prehydrolyzed LHM compared with posthydrolyzed LHM and conventional UHT milk, which, on the other hand, contained higher concentrations of DHA-derived cross-links. Proteomics of collected particles from asymmetrical flow field-flow fractionation in combination with gel electrophoresis indicated the presence of intramicellar cross-links during storage, especially for larger particles involving αS1- and αS2-caseins.